The Interrelationships between REIT Capital Structure and Investment. (15th August 2017) - Alcock, Jamie; Steiner, Eva
Abstract : We explore the interdependence of investment and financing choices in US listed Real Estate Investment Trusts (REITs) in the period 1973–2011. We find that the investment and financing choices of REITs are interdependent, but they are not made simultaneously. Our results suggest that investment determines leverage, but leverage has no apparent effect on investment decisions. Conversely, the debt‐overhang conflict between shareholders and debt holders that theoretically drives the reverse influence of leverage on investment policy does not appear to filter through to the actual investment choices of REITs. Rather, we find that REIT managers utilize the maturity dimension of capital structure to mitigate potential investment distortions and ensure that investment remains on its value‐maximizing path. We also present novel evidence on the role of investments in driving a wedge between REIT target leverage and actual leverage levels, and on the interplay between investments and leverage adjustments toward the target ratio in explaining REIT capital structure dynamics.